Entrepreneurial training and the legitimacy of women entrepreneurs: towards an integrated conceptual model in the Moroccan context - KHATTABI Lamyae; AZMOUR Mohamed (African Scientific Journal, 2025)
Abstract This study aims to model the mechanisms through which entrepreneurial training contributes to the legitimization of women entrepreneurs in a sociocultural context marked by restrictive gender norms, using Morocco as the analytical framework. On a methodological level, the research adopts a theoretical approach based on a systematic literature review. Through this process, an integrated conceptual model is proposed, identifying the direct, mediating (such as self-confidence and access to professional networks), and moderating (notably social norms) effects of training on perceived legitimacy. Although the study is exploratory and conceptual in nature, it lays the groundwork for future empirical validations. The main conclusion highlights that entrepreneurial training serves as a strategic lever not only for developing entrepreneurial skills but also for strengthening the social and institutional recognition of women entrepreneurs, acting as a vector for personal empowerment and the transformation of dominant social norms. Keywords: Entrepreneurial training, Legitimacy, Entrepreneurial skills, Gender, Morocco, Social norms.